Quality, Thermal Behavior and Fatty Acid Compositon of Lipid Extracted from Sardine and Tuna Wastes - Khoddami, Ali (2009)
Fish lipid contains long-chain n-3 (Omega-3) PUFA, particularly EPA (eicosapentaenoic acid, C20:5) and DHA (docosahexaenoic acid, C22:6). Consumption of these PUFAs has been perceived to be important in human nutrition, health, and disease prevention. In this context, there is significant demand for fish lipid. Currently, fish lipid is extracted from fish muscle or liver of herring, mackerel and cod. Sardine and tuna, which are important industrial fishes, produce substantial amount of wastes. The waste of Sardinella lemuru and Euthynnus affinis consist of head, intestine and liver. Therefore the target of the study was to extract the n-3 essential fatty acid rich lipid from the waste with modified Kinsella extraction method by using chloroform-methanol (toxic solvent) and hexane-acetone extraction method by using hexane-acetone (less toxic solvent) and establish the physico-chemical properties of the lipid with a view to use as nutritional supplement or other prospective applications. The yield of extraction, free fatty acid content (FFA), peroxide value (PV), anisidine value (AV), saponification value (SV), iodine value (IV) and lipid composition (neutral and polar lipid) of the extracted lipid from these two fish species wastes (head, intestine and liver) were determined. Thermal behavior (cooling and melting points) and fatty acid composition of the respected lipid were also evaluated. The yield of lipid extraction of S. lemuru liver showed the highest value than head and intestine in both extraction methods. E. affinis head lipid yield indicated significant difference (P < 0.05) with other lipids abstracted from intestine and liver in both extraction methods. Among different lipid sources (head, intestine and liver), the free fatty acid, peroxide value and anisidine value significantly increased (P < 0.05) from head to liver. This increase was observed in all lipid samples extracted by hexane-acetone. The saponification value of the waste lipid samples were in the range of 108 – 197 but significant increases were observed in waste lipid extracted by hexane-acetone. The highest iodine value was found in head lipid in both fish species with significant changes (P < 0.05) with other waste lipid samples in both extraction methods. Higher polarity of solvent used for lipid extraction (chloroform-methanol) increased the extracted polar lipid in fish waste lipid than lower polarity solvents (hexane-acetone). Fifteen fatty acids (FA) were determined from all waste samples except sardine intestine. The major fatty acid were: palmitic (C16:0), oleic (C18:1) and docosahexaenoic (C22:6) acids. The fish waste lipids showed similar fatty acid composition but the proportion of the fatty acids differ. Among different lipid sources, highest concentration of PUFA especially n-3 fatty acids were detected in head lipid samples. The concentration of respective PUFA was in lower content in lipid extracted by hexane-acetone. The n6 / n3 fatty acid ratio of the respective head, liver and intestine lipid samples showed values lower than 1. Differential scanning calorimetery results for fish waste lipid samples indicated that higher unsaturation in lipid sample showed lower cooling and melting temperature.